Synthesis of Chiral 1, 4‐Benzodioxanes and Chromans by Enantioselective Palladium‐Catalyzed Alkene Aryloxyarylation Reactions. Issue 16 (16th March 2016) - Hu, Naifu; Li, Ke; Wang, Zheng; Tang, Wenjun
Abstract: A highly enantioselective alkene aryloxyarylation led to the high‐yielding formation of a series of 1, 4‐benzodioxanes, 1, 4‐benzooxazines, and chromans containing quaternary stereocenters with excellent enantioselectivity. The sterically bulky and conformationally well defined chiral monophosphorus ligandL4 orL5 was responsible for the high reactivity and enantioselectivity of these transformations. The application of this method to the synthesis of the chiral chroman backbone of α‐tocopherol was demonstrated. Abstract : One P is plenty : A sterically bulky and conformationally well defined chiral monophosphorus ligand enabled the highly enantioselective synthesis of a series of O heterocycles containing a quaternary stereocenter by alkene aryloxyarylation (see scheme; X=O, C, N). The application of this transformation to the synthesis of the chiral chroman backbone of α‐tocopherol is demonstrated.